Prevalence of primary dysmenorrhea and its related dietary, anthropometric, menstrual, sociodemographic factors in Isfahan Medical Sciences University, Iran - Habibi, Nahal (2014)
Women make up approximately half of the global population. Dysmenorrhea is one of the common health problems that can affect negatively different dimensions of women’s life and incur economic losses for communities. Thus this cross-sectional study was conducted from January 2013 until April 2013 to determine the prevalence of primary dysmenorrhea and factors associated with its intensity among undergraduate female students of Isfahan University of Medical Sciences, Iran. A total of 311 undergraduate female students who were studying at Isfahan University of Medical Sciences participated in this study. In the present study several instruments include (1) Socio-demographic information questionnaire, (2) 0-10cm Numeric Pain Rating Scale questionnaire, (3) Menstrual characteristics questionnaire, (4) Pictorial Blood Assessment Chart questionnaire, (5) 3day 24hour food recall, (6) Meal skipping questionnaire , (7) “PLUSAVIS 333” body composition analyzer to measure the weight and body fat mass, (7) SECA body meter for measuring the height, (8) stretchresistant tape for measurement the waist circumference and hip circumference were used. Prevalence of primary dysmenorrhea was 89.1% and the intensity of primary dysmenorrhea was reported as mild by 30.3%, moderate by 36.5% and severe by 33.2% (Mean± SD= 4.7± 3.00). There was significant association between younger age of participants (r=-0.233, p< 0.001), lower mother’s years of formal education (r=-0.143, p<0.05), and home residing ( = 16.8, p<0.001) with the higher intensity of primary dysmenorrhea. In addition, lower bleeding intensity (r=0.225, p<0.001), longer interval between periods (r=-0.202, p<0.01), and negative family history of dysmenorrhea ( = 28.09, p<0.001) were significantly associated with the lower intensity of primary dysmenorrhea. Moreover, association between lower body fat percentage (r=-0.245, p<0.01), lower BMI (r=-0.226, p<0.01), smaller waist circumference to height ratio (r=-0.222,p<0.01), smaller waist circumference (r=-0.180, p<0.01), and smaller waist to hip circumference ratio (r=-0.122, p<0.05) with the higher intensity of primary dysmenorrhea were found. Meanwhile, lower calcium intake (r= - 0.238, p<0.01), lower magnesium intake (r= -0.235, p<0.001), and meal skipping ( = 14.611, p <0.001) were positively associated with the higher intensity of primary dysmenorrhea. However, family size, monthly family income, age of menarche, length of menstrual period, dietary intake of fat, protein, energy, fiber, vitamin E, carbohydrate were not significantly associated with the intensity of primary dysmenorrhea. Result of this study showed that positive family history of dysmenorrhea, meal skipping, younger age, lower intake of calcium and magnesium, residing at home, lower body fat percentage, higher bleeding intensity, lower mother’s years of formal education, and shorter interval between periods were factors that significantly contributed to the higher intensity of primary dysmenorrhea ( 0.404; F (10,266) = 19.735, p<0.05). In the current study, family history of dysmenorrhea was the strongest factor that contributed to the intensity of primary dysmenorrhea (β= -0.249; p<0.05) while the weakest factor that contributed to the intensity of primary dysmenorrhea was interval between periods (β= -0.128; p<0.05). In summary, results of this study indicated that primary dysmenorrhea was a common gynecological complaint and some socio-demographic factors, menstrual characteristics, anthropometric indicators, and dietary parameters were significantly contributed toward the intensity of primary dysmenorrhea among undergraduate female students of Isfahan University of Medical Sciences. Hence, particular consideration should be paid to primary dysmenorrhea as a common health problem among young women and some attention to the associated factors can be helpful. For instance, positive family history of dysmenorrhea, younger age, and heavier menstruation are the signs that can help the healthcare providers to recognize high-risk young university students and focus intervention programs to reduce their pain. Individuals must investigate primary dysmenorrhea and consult specialists to reduce suffering from this problem. Moreover, they should try to have suitable diet with enough intakes of energy, macronutrients, and micronutrients. They should also have daily meals and avoid meal-skipping in order to have good nutritional practices. Additionally individuals should try to be fit and where necessary consult specialists including nutritionists and dietitians and avoid wrong models of fitness and wrong methods of dieting. Further research is needed to support the results of this study and to investigate the other contributed factors to the intensity of primary dysmenorrhea.